SOLITARY FIBROUS TUMOUR OF THE THYROID: A CASE REPORT. (February 2015) - Singh, Manisha; Adams, Stuart
Abstract : A 37-year-old female presented with a painless slow growing neck mass. The right thyroid lobe was excised including a discrete spindle cell lesion. Microscopically, the lesion was composed of bland spindle cells arranged in storiform, fascicular and 'patternless' areas with alternating zones of hyper- and hypocellularity. Additionally, keloid-like collagen and a haemangiopericytomatous vascular pattern were also noted. The lesion had an infiltrative growth pattern with entrapped normal thyroid follicles both in the centre and at the periphery of the lesion. There was no marked nuclear pleomorphism or necrosis. Immunohistochemistry studies showed the lesional cells to be positive for vimentin, CD34, CD99, BCL2 and STAT6 and negative for AE1/AE3, CAM5.2 and TTF1. The morphology and immunoprofile confirmed a diagnosis of a solitary fibrous tumour.